Cría en laboratorio de las “joyas vivientes” de El Salvador, Evenus regalis (Cramer) y Evenus batesii (Hewitson) (Lepidoptera: Lycaenidae) - Sermeño-Chicas, J. M.; Robbins, R. K.; Gámez-Alas, J. A.; Lamas, G. (Universidad de El Salvador. Facultad de Ciencias Agronómicas, 2024)
The neotropical genus Evenus Hübner (Lycaenidae:Stearn), and caimito (Chrysophyllum cainito L.) (Sermeño,Eumaeini) of butterflies occurs from Mexico to southern 2009). The field collection and laboratory breeding of the Brazil, mainly in lowland forests and contains 12 species (Robbins, 2004b). Evenus is characterized (Robbins, 2004a) by its unique androconial structures, their reproductive organs and because its larvae feed on plants of the family Sapotaceae which is unique within the Eumaeini tribe except for the species Paiwarria umbratus (Geyer) (Jörgensen, 1934, 1935 Lima, 1936; Hoffman, 1937; Schultze-Rhonhof, 1938; Zikán, 1956; Silva et al., 968; Kendall, 1975; Janzen and Hallwachs, 2012). Three species of Evenus occur in northern Central America: E. regalis (Cramer), E. coronata (Hewitson) and E. batesii (Hewitson). Only the first one is registered in El Salvador, where it was bred on Sapotaceae (Sermeño, 2009). Evenus batesii (Hewitson) has not been bred so far. The purpose of this document is to present the first record of breeding E. batesii and the first record of it in El Salvador. The immature stages of E. batesii versus E. regalis are also compared.